2020
DOI: 10.21203/rs.3.rs-36835/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of Major Lower Extremity Amputations in Individuals With Diabetes in Austria, 2014-2017: A Retrospective Analysis of Health Insurance Database

Abstract: Background: Previous data show a high incidence of major lower extremity amputations (LEA) in Austria. Moreover, recent data on the epidemiology of major LEA are sparse in the Country. This study estimated the incidence and mortality rates of major LEA and assessed risk factors of post major LEA mortality in individuals with diabetes.Methods: A retrospective cohort analysis of 507,180 individuals with diabetes enrolled in the Austrian Health Insurance between 2014 and 2017 was performed. Crude and age-standard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In 2018, the Swedish Amputation and Prosthetics Registry for the Lower Extremity (SwedeAmp) reported more than 80% of amputations as being due to PVD and/or DM, an average age at amputation of 74 years and a 6-month mortality of 19%. 18 These numbers corroborate recent Austrian, 19 Danish, 20 and German 21 data and highlight the need for research to prioritize these elderly comorbid individuals. In Sweden, prescriptions of MPKs are rare among those older than 65 years as indicated by unpublished figures from SwedeAmp showing that approximately 1.5% were prescribed an MPK for the first ever prosthesis and 7% for a later prosthesis during the years 2016–2020.…”
Section: Introductionsupporting
confidence: 73%
“…In 2018, the Swedish Amputation and Prosthetics Registry for the Lower Extremity (SwedeAmp) reported more than 80% of amputations as being due to PVD and/or DM, an average age at amputation of 74 years and a 6-month mortality of 19%. 18 These numbers corroborate recent Austrian, 19 Danish, 20 and German 21 data and highlight the need for research to prioritize these elderly comorbid individuals. In Sweden, prescriptions of MPKs are rare among those older than 65 years as indicated by unpublished figures from SwedeAmp showing that approximately 1.5% were prescribed an MPK for the first ever prosthesis and 7% for a later prosthesis during the years 2016–2020.…”
Section: Introductionsupporting
confidence: 73%
“…Multiple studies have demonstrated that CCI has predictive value in patients with LE pathology. 32 33 34 36 37 However, to date, there is no clear consensus on the most useful risk stratification method to predict postoperative adverse outcomes in elderly patients who are undergoing LE free-flap reconstruction. Therefore, the purpose of this study is to compare the utility of CCI and mFI-5 in predicting postoperative morbidity in comorbid elderly patients undergoing FTT reconstruction for lower limb salvage.…”
mentioning
confidence: 99%
“…Multiple studies have demonstrated that CCI has predictive value in patients with LE pathology. [32][33][34]36,37 However, to date, there is no clear consensus on the most useful risk stratification method to predict postoperative adverse outcomes in elderly patients who are undergoing LE free-flap reconstruction.…”
mentioning
confidence: 99%